Study guides

☆☆

Q: What is the correct answer when you factor 6a2 plus 3a?

Write your answer...

Submit

Still have questions?

Related questions

6a2 + 5ab - 6b2 = (3a - 2b)(2a + 3b)

(2a - 1)(3a + 4)

6a2 + 5ab - 6b2 = 6a2 + 9ab - 4ab - 6b2 = 3a(2a + 3b) - 2b(2a + 3b) = (2a + 3b)*(3a - 2b)

(3a - 2b)(2a + 3b)

2a(3a - 4b + 1)

= 3 X 2 = 6 = a X a = a2 (a square) = 6a2 + 5 Answer

You would factor 3a + 9b as: 3(a+3b)

6a2 - 8ab + 2aas you can see a is common to all terms. And 2 is a factor of 6,8, and 2. So 2a is a factor of all three terms:2a(3a-4b+1)

Considering the minus sign between 5ab and 6b2 then we have the polynomial as 6a2 + 5ab - 6b2. The polynomial is a quadratic polynomial.Steps to factorize a quadratic polynomial:1 - Multiply first term by third term. 6a2 x (-6b2) = -36a2b22 - If possible break the second term into two terms such that they multiple to -36a2b2. If not then it is factorized by Sridharacharya's formula.5ab can be broken as 9ab + (-4ab).These two terms multiply to give -36a2b2.So we can write 6a2 + 5ab - 6b2 = 6a2 + 9ab + (-4ab) - 6b2.6a2 + 9ab - 4ab - 6b2 = 3a(2a + 3b) - 2b(2a + 3b) = (2a + 3b)(3a - 2b).So the factors are (2a + 3b) and (3a - 2b).

6a2

9a^2 + 42at + 49t^2 = (3a + 7t)(3a + 7t)

(3a - 4)(3a - 4)

(6a3 - 19a2 + 15a)/(2a - 3) = a(6a2 - 19a + 15)/(2a - 3) = a(2a - 3)(3a -5)/(2a -3) = a(3a - 5)

(x + 3)(a + b)

(2a+1)(a+1)

a(a^2 - 9a + 3)

The GCF is a.

3a+ax+3b+bx = 3(a+b)+(a+b)x = (a+b)(3+x)

7a minus 2, if "3a-2" means 3a minus 2. 3a plus 1 and 1-3rd in parenthesis times 3a, if "3a-2" means 3a squared. a plus 3a squared plus 3a = 1-3rd times 3a plus 3a times 3a plus 1 times 3a = 3a plus 1 and 1-3rd in parenthesis times 3a

(b + 3)(a + c)

a(b+3)+b(b+3)

5(3a - 5b + 4)

a(2y - 1)(y + 3)

3a(b+c)+2b(b+c)

(3a - 2c)(b - d)